2002
DOI: 10.1200/jco.2002.20.3.699
|View full text |Cite
|
Sign up to set email alerts
|

Does Menopausal Hormone Replacement Therapy Interact With Known Factors to Increase Risk of Breast Cancer?

Abstract: We found no evidence that the risk of breast cancer associated with EPRT is limited to subgroups of women with specific cofactors. Tumors in EPRT users are more often hormone receptor--positive, indicating that they may have a better prognosis than breast cancer overall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
31
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 21 publications
7
31
0
1
Order By: Relevance
“…Several studies have suggested that EPRT is associated with greater increases in risk in leaner than heavier women [5,8], which is consistent with the collaborative reanalysis of the world's data [17]. Other studies have reported similar increases in risk in lean and heavy women [20,23]. Increases in risk have been noted for both testosterone-derived progestins [7,8] and progesterone-derived progestins [5,6],[18-20,22].…”
Section: Hormone Replacement Therapy and Breast Cancer Risksupporting
confidence: 73%
“…Several studies have suggested that EPRT is associated with greater increases in risk in leaner than heavier women [5,8], which is consistent with the collaborative reanalysis of the world's data [17]. Other studies have reported similar increases in risk in lean and heavy women [20,23]. Increases in risk have been noted for both testosterone-derived progestins [7,8] and progesterone-derived progestins [5,6],[18-20,22].…”
Section: Hormone Replacement Therapy and Breast Cancer Risksupporting
confidence: 73%
“…Previous studies have provided discrepant results regarding how the administration of progestins in EPT affects breast cancer risk, with some showing higher risks associated with continuous therapy (10, 14, 16, 21, 34, 45, 46, 5456), another showed a higher risk associated with sequential therapy (15), and still others showing no major differences in the two regimens (9, 12, 13, 18, 29, 47). We found somewhat stronger associations for continuous than sequential EPT use, particularly for current and long-term use.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported stronger hormone associations for invasive lobular than ductal tumors tumors (9–13, 25, 27, 2934). Few epidemiological studies, however, have been able to assess associations according to newer diagnostic criteria which incorporate classification of mixed ductal-lobular carcinomas as well as the more conventional categories of ductal and lobular tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other published works on this topic were based on case-control study designs,7-11,15-17 for which stratum-specific absolute risks are not observed. Nevertheless, we can evaluate departures from additivity by assessing the relative excess risk for interaction (RERI) 23.…”
Section: Discussionmentioning
confidence: 99%